Sintesis dan Karakterisasi Struktur dan Sifat Fluresensi Nanokomposit Fe3O4/CQD@ZIF-8 - Chika Yandora; Astuti Astuti; Dwi Puryanti (Universitas Andalas, 2026)
Advances in nanotechnology are driving the development of multifunctional materials, one of which is magnetic-luminescent nanocomposites that combine magnetic and fluorescent properties in a single system. These materials hold great potential for biomedical applications, particularly in bioimaging. Fe₃O₄ nanoparticles are widely used as magnetic materials due to their biocompatibility and low toxicity, while Carbon Quantum Dots (CQDs) are used as luminescent materials because they exhibit strong fluorescence, high photostability, and are non-toxic. However, Fe3O4/CQD nanocomposites suffer from particle agglomeration and quenching effects. To address these issues, encapsulation was performed using Zeolitic Imidazolate Framework-8 (ZIF-8), which possesses biocompatible, biodegradable properties, and high surface area and porosity. In this study, Fe₃O₄/CQD@ZIF-8 nanocomposites were synthesized. Coating with ZIF-8 is expected to act as a protective layer that has the potential to reduce agglomeration and minimize the quenching effect. The crystalline structure and functional groups of the material were characterized using X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR), while its optical properties were analyzed using fluorescence spectroscopy.